Diagnostic Approach of New-Onset Pancytopenia: Study from A Tertiary Care Center: Pancytopenia 2 Years Retrospective Study - Kumar, Vijay; Khare, Manika; Kishore, Manjari; Sharma, Megha; Marwah, Sadhna; Nigam, A.S.; Singh, Pratap (Annals of Pathology and Laboratory Medicine, 2018)
Background: Pancytopenia is a disorder associated with decrease in number of all three major formed elements of blood (red blood cells, white blood cells and platelets). It is a triad of findings resulting from many disease processes. This may be associated with various hematopoietic and non-hematopoietic condition involving the bone marrow. The management and prognosis of patients with pancytopenia is based on the severity of pancytopenia and the underlying disease process. The present study helps in highlighting the role of various laboratory parameters in conjunction with clinical findings in evaluation of these patients. Methods: The present retrospective study was done for 2 years from April 2015 to April 2017 in Department of Pathology. A total of 210 patients with pancytopenia were included in the study. A detailed history and hematological findings including the bone marrow findings and flow cytometric results were noted in these patients, wherever available. Result: Out of 210 patients, 136 were adults and 74 were children. The mean age of the patients was 42 years. The male to female ratio was 2.7:1. The most common clinical feature in our study was pallor (in all cases) followed by fatigue (70.9%). Most of the cases had severe anemia (57.8%). Megaloblastic anemia was found to be the most common cause, constituting 61.9% of all cases, followed by hypersplenism (25.7%), aplastic anemia (9%), leukemia (1.9%). Occasional cases of kala-azar, typhoid and malaria was also noted. Conclusion: A proper clinico-hematological examination aids in making a proper diagnosis in patient presenting with pancytopenia. Sometimes, specific clinical features point towards a certain disease process. Various laboratory parameters can help in diagnosing the underlying disorder leading to pancytopenia. This diagnostic approach will facilitate to highlight the significance of various diagnostic modalities.